Biological factors involved in alveolar bone regeneration: Consensus report of Working Group 1 of the 15th European Workshop on Periodontology on Bone Regeneration. (18th June 2019) - Giannobile, William V.; Berglundh, Tord; Al‐Nawas, Bilal; Araujo, Mauricio; Bartold, P. Mark; Bouchard, Philippe; Chapple, Iain; Gruber, Reinhard; Lundberg, Pernilla; Sculean, Anton; Lang, Niklaus P.; Lyngstadaas, Petter; et al.
Abstract: Background and Aims: To describe the biology of alveolar bone regeneration. Material and Methods: Four comprehensive reviews were performed on (a) mesenchymal cells and differentiation factors leading to bone formation; (b) the critical interplay between bone resorbing and formative cells; (c) the role of osteoimmunology in the formation and maintenance of alveolar bone; and (d) the self‐regenerative capacity following bone injury or tooth extraction were prepared prior to the workshop. Results and Conclusions: This summary information adds to the fuller understanding of the alveolar bone regenerative response with implications to reconstructive procedures for patient oral rehabilitation. The group collectively formulated and addressed critical questions based on each of the reviews in this consensus report to advance the field. The report concludes with identified areas of future research.